NOTE ON THE CONTROL OF PREDATORY AQUATIC INSECTS IN NURSERY PONDS - Prasad, R R (Indian Journal of Fisheries, 2011)
The efficacy of kerosim oM in the contrail of aquatic insects causing considerable damage to oaitip fry in the Hungary iponds has been tested and’ found equally good! with other existing methods